Pengaruh Job stress dan Happiness at work Terhadap Kinerja Karyawan (Studi di Sekolah Al Zahra Indonesia) - Dharmajati, Erthride Maharai Puri; Mukrodi, Mukrodi (Universitas Muhammadiyah Metro, 2025)
The purpose of this research is to determine the effects of Job Stress and Happiness at Work on Employee Performance. The study was conducted using a quantitative method, with data collected through questionnaires distributed to 35 employees of Al Zahra Indonesia School. In this research, the sampling method used is Simple Random Sampling. The data analysis method employed is Regression Analysis using SPSS 27. The results of the research show that the Job Stress variable has a negative effect on Turnover Intention, while Happiness at Work has a positive effect on Employee Performance.